30. COMPARISON OF RISK BEHAVIORS AND METABOLIC RISK FACTORS OF NON-COMMUNICABLE DISEASES AMONG MANUAL WORKERS IN SOME REGIONS OF THUA THIEN HUE PROVINCE (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the current risk factors of Non-communicable diseases (NCDs) and its comparison among some ecological regions in Thua Thien Hue Province.Subjects and research Methods: A cross-sectional study was applied for this study design. Data were collected from 10/2023 to 12/2023. Tool based on the WHO’s STEPS questionaire for assessing non-communicable diseases and their risk factors was used, including: consuming tobacco and alcohol, physically inactive, unhealthy diet, hypertesion, overweight/obesity, diabetes and dyslipidemia.Results: Smoking, moderate alcohol consumption, insufficient consumption of green vegetables/ fruits, and high salt intake accounted for 29.8%; 96.8%; 70.2%; 77.8% and 16.5%, respectively. The rates of overweight/obesity, diabetes, hypertension and dyslipidemia accounted for 23.2%; 5.1%; 43.7% and 58.9%, respectively. Dietary intake of vegetables/fruits, physical activity, overweight/obesity and diabetes differed between ecological regions.Conclusion: The risk factors of NCDs are different among three ecological regions of the province. Therefore, it needs various appropriate intervention approaches to reduce NCDs risk factors in each region.
Keywords: Non-communicable disease; rick factors; hypertension; diabetes; dyslipidemia